2019
DOI: 10.4238/gmr18193
|View full text |Cite
|
Sign up to set email alerts
|

Research Article Adaptability and stability of corn hybrids in the off season across various agricultural regions in Brazil

Abstract: We evaluated how genetic x environment (G x E) interactions affect grain productivity in corn hybrids grown in traditional and non-traditional environments in the off or "second" season. Adaptability and stability of the hybrids was examined by parametric, nonparametric and multivariate methods. In 2016, 24 hybrids were evaluated in seven environments, in 2017, 13 hybrids were evaluated in six environments. The environments were located between the regions of Southwestern and Southeast Goiás state; Triângulo M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Additionally, low rainfall was recorded in Paraiso between 20/12/2018 and 10/01/2019, when plants were in the stage at which their yield potential is defined. Mijone et al (2019) found that unfavorable environments may result from an inadequate climate or limited use of technology and resources.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, low rainfall was recorded in Paraiso between 20/12/2018 and 10/01/2019, when plants were in the stage at which their yield potential is defined. Mijone et al (2019) found that unfavorable environments may result from an inadequate climate or limited use of technology and resources.…”
Section: Resultsmentioning
confidence: 99%
“…Environmental stratification and the identification and use of cultivars with high adaptability and stability are alternatives to mitigate the effect of interaction (C × E) (Mijone et al, 2019). Identifying similar environments streamlines breeding programs and lowers costs because it allows breeders to eliminate similar environments within each group without compromising the efficiency and precision of the selection process (Cruz & Regazzi, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…A second field study was conducted from April to September 2019 in an area located close to where Field study 1 took place. We used 13 commercial hybrids (S2 Table ), widely used in the region [34][35][36][37][38][39][40][41][42][43][44], with cycle is semi-early, early or super-early, single-cross and double-cross. In three randomized blocks and two treatments: Control-NK addition (20 kg.ha -1 (N): 0 (PO 4 ): 33.2 kg.ha -1 (K)), or NPK fertilization (20 kg.ha -1 (N): 51.6 kg.ha -1 (PO 4 ): 33.2 kg.ha -1 (K)).…”
Section: Field Studymentioning
confidence: 99%